2015
DOI: 10.3906/biy-1402-69
|View full text |Cite
|
Sign up to set email alerts
|

Identification and pathogenicity of bacteria in the Mediterranean corn borerSesamia nonagrioides Lefebvre (Lepidoptera: Noctuidae)

Abstract: IntroductionCorn is the largest grown cereal crop in the world with doubled grain yield per unit area compared to wheat and barley. Although corn production holds second place in Mediterranean agricultural production, there has been a sharp decline in this value due to infestation by the Mediterranean corn borer (Özcan, 2009). The Mediterranean corn borer, Sesamia nonagrioides (Lefebvre) (Lepidoptera: Noctuidae), is a major multivoltine pest of maize in Mediterranean countries (Tsitsipis, 1988;Alexandri and Ts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…Microbacterium species interact with insects. Of these bacteria, Microbacterium testaceum and M. thalassium were isolated from Ostrinia nubilalis (Hübner, 1796) (Lepidoptera: Pyralidae) larvae, Microbacterium arborescens from Sesamia nonagrioides (Lefèbvre, 1827) (Lepidoptera: Noctuidae) and M. liquefaciens were isolated from Dendroctonus micans (Kugelann, 1794) (Coleoptera: Curculionidae) (Yaman et al, 2010;Secil et al, 2012;Eski et al, 2015). In the present study, Microbacterium sp.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Microbacterium species interact with insects. Of these bacteria, Microbacterium testaceum and M. thalassium were isolated from Ostrinia nubilalis (Hübner, 1796) (Lepidoptera: Pyralidae) larvae, Microbacterium arborescens from Sesamia nonagrioides (Lefèbvre, 1827) (Lepidoptera: Noctuidae) and M. liquefaciens were isolated from Dendroctonus micans (Kugelann, 1794) (Coleoptera: Curculionidae) (Yaman et al, 2010;Secil et al, 2012;Eski et al, 2015). In the present study, Microbacterium sp.…”
Section: Discussionmentioning
confidence: 99%
“…Serratia marcescens, non-pathogenic at low-density, pass into hemocoel, multiply there and kill the insect in 1 to 3 d (Sikorowski et al, 2001). Serratia marcescens common in insects is commonly isolated from several pests of Lepidoptera and Coleoptera (Cakici et al, 2014;Eski et al, 2015;Pu & Hou, 2016;Bidari et al, 2018). However, there are no records on the isolation of this bacteria from the whiteflies.…”
Section: Discussionmentioning
confidence: 99%
“…Laboratory bioassays using pure Cry1Ab endotoxin from Bt to establish baseline susceptibility of O. nubilalis and S. nonagrioides have indicated that S. nonagrioides is at least as susceptible to this toxin as O. nubilalis (González-Núñez et al 2000). According to Eski et al (2015), Bt and B. safensis caused 93 and 80% mortality in S. nonagrioides larvae, respectively. However, the most widespread and successful application of Bt was achieved with the introduction of genetically engineered crops (see Bt technology and varietal resistance section).…”
Section: Entomopathogenic Bacteriamentioning
confidence: 99%